2019
DOI: 10.1080/24750573.2019.1583481
|View full text |Cite
|
Sign up to set email alerts
|

Cortico-thalamo-striatal circuit components’ volumes and their correlations differ significantly among patients with obsessive–compulsive disorder: a case–control MRI study

Abstract: AIM: In the present study, we aimed to determine the volume differences in brain regions involved in cortical-striatal-thalamic-cortical circuit (CSTC) between healthy subjects and obsessive-compulsive disorder (OCD) patients. We also evaluated the potential relationship between volumes of region of interest and various illness parameters (duration and current severity OCD, and the influence of drug treatment). METHODS: We examined the volumetric differences in dorsolateral prefrontal cortex (DPFC), orbitofron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…The thalamus is a key region within the CSTC circuit, and thalamic-cortical dysconnectivity has been reported in OCD [36]. Increased gray matter volume and FC in the thalamus have been observed in OCD [8,[37][38][39][40]. Degree values of weighted networks are more resilient to FC disturbances, which are referred to as FC strength [15].…”
Section: Discussionmentioning
confidence: 99%
“…The thalamus is a key region within the CSTC circuit, and thalamic-cortical dysconnectivity has been reported in OCD [36]. Increased gray matter volume and FC in the thalamus have been observed in OCD [8,[37][38][39][40]. Degree values of weighted networks are more resilient to FC disturbances, which are referred to as FC strength [15].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to striatal anatomic alterations (Dogan, Ertekin, Turkdogan, Memis, & Sevincok, 2019), there are also reports of decreased volume in the thalamus in OCD (Tang et al, 2016). These observations parallel findings from fMRI studies in OCD that found decreased fractional ALFF (Qiu et al, 2017) and regional homogeneity (Niu et al, 2017) in the thalamus, and decreased ALFF in caudate (Tang et al, 2016), the hypofunction of which were correlated with symptom severity of OCD (Dogan et al, 2019; Qiu et al, 2017). This might lead to the attenuated inhibitory influence of the left thalamus and caudate on left pACC in the present study, but also raises questions about the neurobiological mechanisms for how CSTC circuit alterations might contribute to decreased activity at rest and increased task‐related activation in this structure.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of caudate is considered a common neural feature of OCD (Graybiel & Rauch, 2000). In addition to striatal anatomic alterations (Dogan, Ertekin, Turkdogan, Memis, & Sevincok, 2019), there are also reports of decreased volume in the thalamus in OCD (Tang et al, 2016). These observations parallel findings from fMRI studies in OCD that found decreased fractional ALFF (Qiu et al, 2017) and regional homogeneity (Niu et al, 2017) in the thalamus, and decreased ALFF in caudate (Tang et al, 2016), the hypofunction of which were correlated with symptom severity of OCD (Dogan et al, 2019; Qiu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact mechanisms are unknown, numerous vital components have been identified. It is considered that a critical role is played by dysfunction in the cortico-striato-thalamo-cortical (CSTC) circuit, which involves communication between the prefrontal cortex, basal ganglia, and thalamus 12 14 . Neurotransmitters such as serotonin, dopamine, and glutamate are implicated in OCD pathogenesis 9 .…”
Section: Introductionmentioning
confidence: 99%